Comparison of the Chromosome Structures between the Chicken and Three Anserid Species, the Domestic Duck (Anas platyrhynchos), Muscovy Duck (Cairina moschata), and Chinese Goose (Anser cygnoides), and the Delineation of their Karyotype Evolution by Comparative Chromosome Mapping - Fhamida B. Islam; Yoshinobu Uno; Mitsuo Nunome; Osamu Nishimura; Hiroshi Tarui; Kiyokazu Agata; Yoichi Matsuda (The Journal of Poultry Science, 2014)
To better understand the process of karyotype evolution in Galloanserae (Galliformes and Anseriformes), we performed comparative chromosome painting with chicken chromosome-specific DNA probes and FISH mapping of the 18S-28S ribosomal RNA (rRNA) genes, telomeric (TTAGGG)n repeats, and cDNA clones of 37 genes for three anserid species, the domestic duck (Anas platyrhynchos), Muscovy duck (Cairina moschata), and Chinese goose (Anser cygnoides). Each chicken probe of chromosomes 1-9 and the Z chromosome painted a single pair of chromosomes in the three species except for the chromosome 4 probe, which painted acrocentric chromosome 4 and a pair of microchromosomes. The 18S-28S rRNA genes were localized to four pairs of microchromosomes in the domestic duck and Muscovy duck, and eight pairs of microchromosomes in the Chinese goose. The (TTAGGG)n repeats were localized to both telomeric ends of all chromosomes in the three species, and were additionally located in the interstitial region of the short arm of chromosome 1 in the domestic duck and in the centromeric region of chromosome 1 in the Muscovy duck. Comparative gene mapping of 37 chicken chromosome 1-4-linked and Z-linked genes revealed high chromosome homologies among three anserid species and also between the chicken and the three anserid species, although there were several chromosome rearrangements: pericentric inversion in chromosome 2, pericentric and paracentric inversions or centromere repositioning in the Z chromosome between the chicken and the anserid species, and pericentric inversions in chromosome 4 and the Z chromosome between the Chinese goose and the two duck species. These results collectively suggest that karyotypes have been highly conserved in Anseriformes and that chromosome rearrangements also occurred less frequently between Galliformes and Anseriformes after they diverged around 100 million years ago.